The Meaning of the Police Profession in Batak Tribe Families in Sungai Langkai Village, Batam City - Eva Lasmaria Br Sitanggang; Emmy Solina; Sri Wahyuni (Social Issues Quarterly, 2023)
The purpose of this research is to specifically describe the social status of the police profession by studying the meaning that the Batak tribe family associates with the police profession in Sungai Langkai Village, Batam City. The theory used in this study is the theory of Symbolic Interactionism by Herbert Blumer. This theory rests on three premises: a) Humans act based on the meanings that things have for them, b) These meanings come from a person's social interaction with others, and c) These meanings are refined during the process of social interaction. In this study, researchers used qualitative methods with a descriptive approach. Data collection was carried out using observation, interviews, and documentation methods. The technique of determining informants was purposive sampling with informant criteria, namely families and sons who work as police officers in Sungai Langkai Village, Batam City, and the number of informants in this study is 10. The data analysis techniques included data reduction, data presentation, and conclusion drawing. The results of this study show that the meaning of the police profession in Batak families is multi-faceted. Firstly, it is seen as a way of continuing the clan. Secondly, it increases the social status of the police officer in the family. Thirdly, it enhances personal integrity in the family. Fourthly, it provides a source of income/salary. Fifthly, the profession serves as a role model in the family. The meaning of the police profession in the Batak family is rooted in the belief that the son who becomes a police officer will continue the clan and carry the family's good name at family events. This meaning is reflected in the profession chosen by the family members who work as police officers.